Structure and orientation of water molecules at model hydrophobic surfaces with curvature: From graphene sheets to carbon nanotubes and fullerenes - Alarcon, Laureano Martin (2011)
We study the structure and orientation of water molecules at model hydrophobic surfaces by means of molecular dynamics. We focus here on the role of geometry in water hydration by comparing the situation for a planar graphene sheet with convex surfaces with different curvature: the exterior surfaces of carbon nanotubes and fullerenes of different radii. In all cases, we find the first water hydration layer to be more structured than the bulk. Additionally, the first water layers are found to be well oriented with respect to the surface normal in a way consistent with a local Ice Ih-like structuring, but differently form the water-air interface (along the opposite direction with respect to ice Ih basal plane). We also show that as the curvature of the surface gets more pronounced, the water molecules get less structured and oriented. This monotonic loss of local structure for proximal water represents a smooth tendency whenever we deal with an extended surface. However, when the surface becomes partially or completely non-extended (within the sub-nanometric regime), the surface water layer becomes to quickly lose structuring and orientation.